Kinematics analysis of the lower extremity during the two-handed backhand grounder stroke and drive volley for tennis players - Tai, M. L.; Yang, C. J.; Chang, K. L.; Tang, W. T. (ISBS Proceedings Archive (Michigan), 2018)
This study discussed the motion characteristics of the X-Factor and the role of stance positioning on backhand tennis swing in drive volley and ground stroke. Three elite female tennis players which are training more than 20 hours per week participated in this study. Motion Analysis System with 10 Eagle Digital inferred high speed cameras at 200Hz were used for this study. This study found that the pre-impact rotation mode did not have consistent pattern, but similar trend can be found between the strokes, with the square timing was close at the impact and more trunk rotations on ground stroke in the follow through In the pre-impact stance setting, the ground stroke will adopt a more closed stance, which may be helpful for the hip joint activity. It is suggested that future studies may increase the parameters of the hip joint to establish the reasons for this technical difference.